Influence of Palmitic Acid and Amino Acids Addition on Iturin A Productivity by Bacillus subtilis RB14-CS - YULIAR YULIAR (Biodiversitas Journal of Biological Diversity, 2005)
The aim of this study was to observe the influence of palmitic acid and amino acids on enhancement of iturin A productivity using Bacillus subtilis RB14-CS. The concentrations of palmitic acid examined were 0.8%, 1.6%, and 3.2%. A good yield was observed when 1.6% palmitic acid was added to Polypepton S medium. The production of iturin A increased about 18% than the control. Addition of 3.2% palmitic acid was not effective on iturin A production. It gave lower pH and slightly higher viable cell number of RB14-CS than control and the others addition concentration. Whereas the addition of 0.8% of each of the following amino acids; L-arg, L-asn , L-gln , L-glu, L-gly, Lleu,L-lys, L-trp, L-tyr, and L-val could not increase iturin A productivity, but changed the proportion of iturin A peaks. L-leu, L-val, and L-asn addition produced the highest proportion of peak 3, 4, and 1 respectively.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: iturin A, Bacillus subtilis RB14-CS, palmitic acid, and L-amino acids.